Letter - Lizaso, Jose I. de
012a-0064-001 J.I. de Lizaso, Delegate of the Basque Government. Private Address 75 Gloucester Terrace Hyde Park London W.2 Tel Paddington 5754 30th July, 1938. Sir Walter Citrine, Transport House, Smith Square, S. W. 1. Dear Sir Walter My secretary, Mr. Ramon de la Sota, whom you have met, is leaving shortly for America, sent by the Basque Government to work there for a short time. I wonder if you would be good enough to let me have some letters of introduction for him? I remain Yours sincerely, Jose I. de Lizaso 292/946/12a/64